Processos e Dinâmicas de Intervenção no Espaço Peri-urbano: O caso de Maputo - Sílvia Jorge; Vanessa Melo (Cadernos de Estudos Africanos)
In the current neoliberal context, the socio-spatial inequalities between the urbanized centre and the peri-urban area, that characterize Maputo city since its genesis, are reshaped. In this article are analysed the current processes and dynamics of intervention in the peri-urban space object of greater transformations, namely the areas closest and farthest to the centre. Through the characterization and analysis of representative case studies, it aims to understand how the different types of ongoing intervention relate to the socio-spatial phenomena of segregation and exclusion. These phenomena reveal themselves complex and multifaceted, subject to different levels of understanding and intensity, depending on the specificity of the territories, the processes that transform them and the aspirations and perceptions of the actors involved.